Implementation of Environmental Health Management to Achieve Open Defecation Free in Tamansari Village in Bandung - Raden Ganang Ibnusantosa; Susan Fitriyana; Nurul Romadhona; Titik Respati (Global Medical & Health Communication (GMHC), 2021)
Proper sanitation will ensure the community is healthy and reduce most infectious diseases' transmission, especially water-borne diseases. Open defecation has a significant effect on public health. Sanitation coverage data from the Ministry of Health Republic of Indonesia in 2018 shows that open defecation is still high, including in Bandung city. This study aims to analyze the implementation of environmental health management programs that have been implemented in Tamansari village in Bandung city. This research is a qualitative research conducted in Tamansari village in Bandung city. The data were collected from May to August 2021 through Focus Group Discussion with cadres and in-depth interviews with informants from the village head, a representative from a non-governmental group, and cadres. The results of this study indicate that the process of planning, organizing, mobilizing, and controlling has been running according to the theory. Obstacles faced by the village in achieving open defecation free include funds, land, community understanding, and sub-optimal supervision. PENERAPAN MANAJEMEN KESEHATAN LINGKUNGAN UNTUK MENCAPAI BEBAS BUANG AIR BESAR SEMBARANGAN DI KELURAHAN TAMANSARI BANDUNGSanitasi yang layak akan memastikan masyarakat berada dalam lingkungan yang sehat dan mengurangi sebagian besar penularan penyakit infeksi terutama penyakit yang ditularkan melalui air. Buang air besar (BAB) sembarangan memiliki efek yang sangat besar bagi kesehatan masyarakat. Data cakupan sanitasi dari Kementerian Kesehatan Republik Indonesia tahun 2018 menunjukkan bahwa perilaku BAB sembarangan masih tinggi termasuk di Kota Bandung. Penelitian ini bertujuan menganalisis penerapan program manajemen kesehatan lingkungan yang telah dilaksanakan di Kelurahan Tamansari Kota Bandung. Penelitian ini merupakan penelitian kualitatif yang dilakukan di Kelurahan Tamansari Kota Bandung. Pengambilan data dilakukan pada bulan Mei hingga Agustus 2021 melalui Focus Group Discussion dengan kader dan wawancara mendalam dengan lurah, perwakilan kelompok swadaya masyarakat, dan kader. Hasil penelitian ini menunjukkan bahwa proses perencanaan, pengorganisasian, penggerakan, dan pengawasan sudah berjalan sesuai dengan teori. Kendala yang dihadapi oleh kelurahan dalam mencapai bebas BAB sembarangan antara lain dana, lahan, pemahaman masyarakat, dan pengawasan yang belum optimal.